Legal integration of Islam : a transatlantic comparison - Joppke, Christian (Harvard University Press, 2013)
The status of Islam in Western societies remains deeply contentious. Countering strident claims on both the right and left, Legal Integration of Islam offers an empirically informed analysis of how four liberal democracies--France, Germany, Canada, and the United States--have responded to the challenge of integrating Islam and Muslim populations.